The Relationship Between Total Intravenous Anesthesia Technique and the Incidence of Postoperative Nausea and Vomiting : A Systematic Review - Iffa Refni Ihksan; Anggara Jaka Widiantoro Herliansyah; Wirawan Anggorotomo (The Indonesian Journal of General Medicine, 2026)
Introduction: Postoperative nausea and vomiting (PONV) remains a major cause of delayed recovery and unplanned hospital admission after general anesthesia. Although propofol-based total intravenous anesthesia (TIVA) is often considered to reduce PONV, the magnitude, timing, and moderators of this effect remain debated. Methods: This systematic review synthesized evidence from 80 studies (predominantly randomized controlled trials) comparing TIVA versus volatile or alternative intravenous techniques. Outcomes focused on PONV incidence, severity, rescue antiemetic use, and recovery quality. Results: Propofol-based TIVA significantly reduced early PONV (0–6 h) compared to volatile agents, with absolute risk reductions of 15–18% and number needed to treat of 3–6 in high-risk populations (1,2,4,7). The effect was most pronounced against isoflurane‑nitrous oxide and attenuated but still significant against sevoflurane (RR 0.63) and desflurane (RR 0.35) (14). However, the antiemetic advantage diminished after 6–12 hours, and delayed PONV could be higher with TIVA if long-acting antiemetics were omitted (8,9). Opioid‑free TIVA (propofol‑dexmedetomidine) further reduced PONV beyond propofol‑opioid TIVA (15,16). Remimazolam‑based TIVA produced equivalent PONV reduction to propofol, suggesting that volatile avoidance, not propofol‑specific pharmacology, is the key mechanism (14,18). In 2,010 patients, Visser et al. demonstrated NNT=6 for PONV prevention with TIVA (1). Several large trials confirmed significant early benefits in thyroidectomy (31), bariatric (38), craniotomy (62), and breast surgery (41), with low heterogeneity in the first six postoperative hours. Discussion: The TIVA advantage is real, time‑limited, and context‑dependent. It is largest in high‑baseline‑risk procedures without multimodal prophylaxis, diminishes against low‑emetogenicity volatiles, and disappears by 24 h unless opioid‑free or supplemented with long‑acting antiemetics. Conclusion: Propofol-based TIVA is an effective strategy for reducing early PONV, especially when volatile agents with high emetogenicity would otherwise be used. For delayed PONV, additional prophylactic antiemetics remain necessary irrespective of anesthetic technique.